Tradisi Doa Berantai dan Inklusi Sosial Keagamaan di Desa Kepung Kabupaten Kediri - Asyhabuddin Asyhabuddin (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
This paper seeks to examine the tradition of chain prayer and religious social inclusion in Kepung Village, Kediri Regency. The idea of this paper came from the growing religious conflict. The inhabitants of Kepung village in Kediri, East Java district, have a unique method to build harmonious relations between religions amid the potential conflicts of religious diversity they have. The data were obtained by interviewing people in Kepung Village, Kediri Regency. That method is a tradition of chain prayer which is carried out as a series of village cleaning traditions every month of Sura in the Javanese calendar. This tradition fosters social religious inclusion because this tradition builds inclusive religious attitudes, inclusive religious policies, and guarantees access and active participation of religious social groups. In addition, this tradition also narrows ethnic distance because it can provide the expectations of minority religious groups, thus generating trust between religious groups. Tulisan ini berusaha untuk mengkaji tentang tradisi doa berantai dan inklusi sosial keagamaan di Desa Kepung Kabupaten Kediri. Ide tulisan ini berasal dari semakin berkembangnya konflik keagamaan, warga desa Kepung di kabupaten Kediri Jawa Timur memiliki cara unik untuk membangun keharmonisan hubungan antar agama di tengah potensi konflik keragaman agama yang mereka miliki. Data-data diperoleh dengan wawancara kepada orang-orang di Desa Kepung Kabupaten Kediri. Cara itu adalah tradisi doa berantai yang dilakukan sebagai rangkaian dari tradisi bersih desa setiap bulan Sura dalam penanggalan Jawa. Tradisi ini memupuk inklusi sosial keagamaan karena tradisi ini membangun sikap keagamaan inklusif, kebijakan keagamaan inklusif dan menjamin akses dan partisipasi aktif kelompok minoritas keagamaan. Selain itu, tradisi ini juga mempersempit ethnic distance karena mampu memberikan ekspektasi kelompok keagamaan minoritas, sehingga memunculkan rasa percaya (trust) antar kelompok keagamaan yang ada.